An analysis of the impact of financialization on commodity markets - Ndawona, Takudzwa Maitaishe (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
An unprecedented increase in real commodity prices from 2002-2011 fuelled an intense debate as to the causes of the steep rise in prices and its possible implications for producers and consumers. On the one hand, the prolonged and dramatic rise in almost all commodity prices is attributed to growing demand from emerging market economies, supply shocks such as adverse weather conditions, export bans as well as other macroeconomic factors. Collectively these are known as the fundamental (demand and supply) factors. On the other hand, there is a growing body of evidence that suggests these fundamental factors alone are not sufficient enough to explain recent commodity price developments. It is noted that alongside changes in the fundamental factors, there was a major shift in trading activities on commodity derivative markets related to the increasing presence of financial investors, institutional investors and hedge funds. This had important effects, it is argued, on the microstructure of these markets and on price dynamics in a process termed "fmancialization" . Most of the empirical literature covers the period of rising commodity prices from 20022011. This study seeks to add to the existing literature by examining, in addition, the impact of financialization when commodity prices were falling from 2011-2015. Whereas the literature focuses mainly on the rise of agricultural commodity prices, the focus of this study is on metals, oil and bulk commodities (coal and iron ore). Two techniques are employed, namely the calculation of rolling correlations for futures and spot returns. Granger causality tests are then performed to examine the relationships between futures and spot prices. Rolling return correlations are calculated for i) different exchange- traded commodities and ii) exchange-traded commodities and bulk commodities not traded on exchanges. This is done to establish whether the increased correlations between different commodities found in the literature still hold now that commodity prices across all categories are falling. Granger causality tests are used in order to establish the link between the futures prices and spot prices both during the upswing period (2002-2011) and downswing period (2011-2015). It is found that rapidly growing indexed-based investment in commodity markets (financialization) during the upswing period is concurrent with increasingly correlated returns on the prices of unrelated commodities in both the futures and spot markets. These correlations decline during the period of falling commodity prices (2011-2015). This was a period in which the total amount of commodity assets under management fell sharply. This supports the a priori expectation that if the increased correlations of previously seemingly correlated and unrelated commodities during the upswing had been driven by financialization, the correlation would decline in the downturn. Granger causality results reveal statistically significant evidence of futures prices (returns) driving spot prices (returns) during the financialization period. However, post-financialization there is a shift to more bidirectional relationships. The study therefore concludes that, in addition to changing fundamental and macroeconomic factors, the financialization of commodity markets further drove the excessive and volatile price levels in commodity markets from 2002 to 2011.
Keywords: Uncatalogued